Fuzzy Logic design using VHDL on FPGA - Sham Sagaria a/l Marisinapen (Universiti Malaysia Perlis, 2008)
This fuzzy logic design is to produce 3 outputs from a 7 input. The 7 digital input (3-bits each) is produced from the analogue output of the 7-input honeycomb sensor. The honeycomb sensor receives input from seven sensors which sense light ambient and produces analogue signal to acknowledge the location which receives the highest light ambient. This analogue signal is converted to digital signal and this where the fuzzy logic designs comes. The fuzzy logic receive 7 digital input which provide information on which location the light ambient is high. From this digital input, the fuzzy logic will choose the best behaviour to produce 3 outputs to control the movement of three motors (horizontal, vertical and tilt) which rotates a plate facing the location with the highest light ambient. The fuzzy logic design will produce a 2 output of 3-bits each and 1 output of 4-bits, for each type of movements which it’s MSB represent the direction of the plate rotation and the remaining bits is to indicate the plate rotation degree. The design also should be able to store the current position of the plate to prevent system error on the downstream when it uses the output of this design to rotate the motors. The overall function of this project is to enable reception of maximum sunlight to generate electrical power using solar system.